Decision making in a critical development phase : the TOREAD case - Hao, Chen, (SAGE Knowledge. Cases., 2012)
TOREAD Company, a professional provider of outdoor equipment in China, started its business by producing and selling tents. To meet market demands and follow industry trends, TOREAD expanded its product line ranging from outdoor durable tent products to "Pan-outdoor" products including footwear and clothing. While expanding the product range, TOREAD was challenged by a quality problem in its first batch of shoes forcing management to consider what they should do with the faulty shoes.